Pengaruh Pemahaman Produk Mudharabah dan Ketaatan Syariah terhadap Keputusan Menggunakan Produk Mudharabah pada Lembaga Keuangan Syariah - Madaniah, Mutiara Najmi; Prastiwi, Iin Emy; Nuriana, Mutia Azizah (Lisyabab : Jurnal Studi Islam dan Sosial, 2023)
This research aims to find out how ITB AAS Indonesia sharia economics students' decisions in using sharia financial products are influenced by their knowledge of the product and compliance with sharia law. Indonesia, which has the largest Muslim population in the world, has the potential to become a leader in the Islamic finance sector. Islamic banks are the main facilitators of all economic operations in the halal industrial environment. Utilizing quantitative methodology, this investigation. This research uses multiple linear regression analysis. The two categories of data used are primary and secondary data. The Slovin formula was used to determine the sample size for this investigation, which included 354 participants. A total of 78 samples were collected. The SPSS 23 application was used to analyze the data. The findings show that sharia compliance has a significant effect on the decision to use sharia financial services, while understanding mudharabah products does not have a significant effect on the decision of ITB Islamic Economics students to use sharia financial products.